Pengaruh Pengungkapan Corporate Social Responsibility terhadap Nilai Perusahaan dengan Good Corporate Governance sebagai Variabel Pemoderasi - Putra, Marchall Tondi Saulus; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi; Vol 32 No 5 (2022)DO - 10.24843/EJA.2022.v32.i05.p15, 2022)
This study aims to obtain empirical evidence regarding the effect of Corporate Social Responsibility (CSR) disclosure on firm value with Good Corporate Governance (GCG) as the moderating variable. The scope of research is companies that are included or have been listed in the LQ45 index during the 2012-2019 period. The sample is going to be determined by using purposive sampling technique. The results show that CSR disclosure has a positive effect on firm value, but GCG which is used as a moderating variable actually weakens the effect of CSR disclosure on firm value. The results of this study are expected to be a reference for companies and investors to consider social responsibility more and also become the basis for the development of subsequent studies involving the same variables or research population. Keywords : Corporate Social Responsibility Disclosure; Firm Value; Good Corporate Governance.